Language Styles in Advertisement: National Geographic Cover Planet or Plastic? - Ade Indah Juliyanti; Tiarma Ika Yuliana (JEdu: Journal of English Education, 2022)
Language has the power to influence people and their behavior in many instances, one of which is in the field of advertising. Magazine advertisements are not simply constructed but they are carefully made with many considerations. One of the considerations is that they have the intention to attract readers to buy any products advertised. Magazines in many instances employ more than one language style to produce a splendid advertisement. Magazines have their own way to manifest their ideas to promote a product. Language styles of advertising in magazines play an important role to attract the reader's attention. The purpose of this study is to identify the language styles of advertising employed in National Geographic Magazine and to explore how the delivery of meaning is set to the readers through the language styles of advertisement employed. This study utilizes qualitative descriptive methods and focuses on the theory of Pop. The data were taken from National Geographic Cover: Planet or Plastic? Issue. The results of this study showed that the advertisements in National Geographic Magazine used four language styles: morphological, syntactical, rhetorical, and slogan style. Among these four, the rhetoric style was the most used in this National Geographic Cover